Imaging the Solvation of a One‐Dimensional Solid on the Molecular Scale. Issue 50 (14th November 2018) - Lucht, Karsten; Trosien, Iris; Sander, Wolfram; Morgenstern, Karina
Abstract: We have observed the inversion of the solvation environment of a one‐dimensional solid by low‐temperature scanning tunneling microscopy. Adsorption of 3‐methoxy‐9‐diazofluorene on Ag(111) yields highly oriented supramolecular chains, which are then exposed to water molecules. The annealing of dry and water‐decorated chains results in diametrically opposed outcomes. While the former simply leads to an increase in chain length and number, the latter results in a complete loss of order and produces water clusters decorated with the organic molecule. Abstract : The formation of a one‐dimensional solid, its hydration, and its dissolution on a Ag(111) surface were followed by low‐temperature scanning tunneling microscopy. The annealing of dry chains results in a simple increase in chain length and number whereas the annealing of water‐decorated chains results in a complete loss of order and produces water clusters decorated with the organic molecule.